2018
DOI: 10.1186/s12974-018-1120-x
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminase 1 regulates the release of extracellular vesicles during neuroinflammation through key metabolic intermediate alpha-ketoglutarate

Abstract: BackgroundExtracellular vesicles (EVs) are important in the intercellular communication of the central nervous system, and their release is increased during neuroinflammation. Our previous data demonstrated an increased release of EVs during HIV-1 infection and immune activation in glial cells. However, the molecular mechanism by which infection and inflammation increase EV release remains unknown. In the current study, we investigated the role of glutaminase 1 (GLS1)-mediated glutaminolysis and the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…EV release can be modulated by reactive oxygen species (Blanc et al, 2007), inflammation (Bianco et al, 2005), and by ATP (Savina et al, 2003). Our previous work found that immune activation induced by LPS or TNF-α can increase EV release from microglia and astrocytes, Wu et al, 2015;Wu et al, 2018). In the current study, we used LPS as the inflammationinducing agent for the microglia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…EV release can be modulated by reactive oxygen species (Blanc et al, 2007), inflammation (Bianco et al, 2005), and by ATP (Savina et al, 2003). Our previous work found that immune activation induced by LPS or TNF-α can increase EV release from microglia and astrocytes, Wu et al, 2015;Wu et al, 2018). In the current study, we used LPS as the inflammationinducing agent for the microglia.…”
Section: Discussionmentioning
confidence: 97%
“…EVs can be found in interstitial fluid, cerebrospinal fluid (Vella et al, 2008), circulating blood (Suetsugu et al, 2013), and primarily assert biological function through delivering cytokines, nucleic acids, lipids, and proteins to nearby or distant cells, suggesting that they play an important role in cell-to-cell communication (Thery et al, 2006). EV secretion is increased during neuroinflammation; our previous studies, along with others', have suggested that EVs fuel pathogenic processes in the brain during neuroinflammation (Gupta and Pulliam, 2014;Huang et al, 2018;Wang et al, 2017;Wu et al, 2015;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because our previous findings indicate that GLS1 is a key enzyme in exosomes release of glial cells including microglia and astrocytes in vitro (16,17), we examined whether or not the alteration of exosome release in focal cerebral ischemic brains is mediated by GLS1. NTA demonstrated that GLS1 inhibition by CB839 administration significantly reduced the concentration of exosome in ischemic rat brains vs. the DMSO-treated ischemia group (Figure 5A).…”
Section: Gls1 Mediates Pro-inflammatory Exosome Releasementioning
confidence: 99%
“…For instance, in murine models, intracerebral injection of IL-1β promotes the release of extracellular vesicles from astrocytes, leading to leukocyte migration into the brain and regulation of the liver cytokines profile by inhibition of the peroxisome proliferator-activated receptor α (Dickens et al, 2017). It is important to mention that extracellular vesicles released by central immune activation depend on glutamine modulation by glutaminase enzyme activation (Dickens et al, 2017;Wang et al, 2017;Wu et al, 2018). In fact, substantial programing of metabolic related pathways coordinates innate immunity.…”
Section: Does Central and Peripheral Innate Immune Training By Nlrp3 mentioning
confidence: 99%